Effects of Ectodermal Dysplasia on the Maxilla: A Study of Cone-Beam Computed Tomography - Ünal, Beyza Karadede (Makara Journal of Health Research, 2021)
Background: This study aimed to examine the effects of ectodermal dysplasia (ED) on the transverse width of the maxillary bone. Methods: The ED group was composed of seven people, while the control group consisted of retrospective cone-beam computed tomography images of seven individuals with skeletal class 1 relationship. Images on the sagittal planes were taken, and cross-sections were taken from the longest point of the Anterior Nasal Spine-Posterior Nasal Spine line. The distance between the distal anterior canine teeth from the right buccal cortical bone to the left buccal cortical bone was measured. At the posterior region, the distance between the right point where the pterygoid protrusions and the tuber maxilla fused and the left point was measured. Results: The ED group has significantly narrower (p < 0.05) anterior region than the control group, and no significant difference in the posterior region width was found between the ED group and control group. Conclusions: The quality of life should be improved by awareness of ED in dentistry, by using a professional approach and modern applications such as three-dimensional computed tomography when necessary, and by considering the morphological characteristics of the patients.